Introduction to wavelet transform a signal processing approach - Narasimhan, S.V (Alpha Science International, 2012)
INTRODUCTION TO WAVELET TRANSFORM: A Signal Processing Approach, has been developed in a simple, logical and directed way. To understand this subject, the background required is physics and mathematics at a junior degree level and the basic knowledge of signals and systems. The ease of understanding has been facilitated by providing all the intermediate steps in a mathematical derivation and physical meaning of the mathematical relations, preserving the rigor and depth of the subject.